Mapping Human Rights Due Diligence Regulations and Evaluating their Contribution in Upholding Labour Standards in Global Supply Chains - Bright, Claire (2021)
prepared as part of a research compendium for the International Labour Organization (ILO) with the support of the Government of France and published in G. Delautre, E. Echeverría Manrique and C. Fenwick, Decent work in globalised economy: Lessons from public and private initiatives, ILO 2021, 75-108